2016
DOI: 10.1118/1.4961747
|View full text |Cite
|
Sign up to set email alerts
|

A gate evaluation of the sources of error in quantitative90Y PET

Abstract: Simulations of Y PET confirm that quantitativeY is achievable with the same approach as that used for F, and that there is likely very little margin for improvement by attempting to model aspects unique toY, such as the much higher random fraction or the presence of bremsstrahlung in the singles data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 35 publications
0
18
0
1
Order By: Relevance
“…Y-90 imaging involves SPECT via bremsstrahlung photons or PET via very low probability (~3.2 × 10 −5 ) positrons in the presence of increased singles events from bremsstrahlung photons and gammas from natural radioactivity in Lu-based crystals used in some PET systems. Due to these attributes of Y-90, positive bias in cold regions and underestimation in regions of interest are reported in many Y-90 PET papers (Carlier et al (2015), Pasciak et al (2014) and Strydhorst et al (2016)). Those reports conclude that the bias is introduced by the current standard PET reconstruction algorithms that enforce a nonnegativity constraint in the image domain.…”
Section: Introductionmentioning
confidence: 99%
“…Y-90 imaging involves SPECT via bremsstrahlung photons or PET via very low probability (~3.2 × 10 −5 ) positrons in the presence of increased singles events from bremsstrahlung photons and gammas from natural radioactivity in Lu-based crystals used in some PET systems. Due to these attributes of Y-90, positive bias in cold regions and underestimation in regions of interest are reported in many Y-90 PET papers (Carlier et al (2015), Pasciak et al (2014) and Strydhorst et al (2016)). Those reports conclude that the bias is introduced by the current standard PET reconstruction algorithms that enforce a nonnegativity constraint in the image domain.…”
Section: Introductionmentioning
confidence: 99%
“…The use of correct point spread function (PSF) modeling and TOF reconstruction kept background variability and noise at acceptable levels [ 98 ]. This was further corroborated in a fully Monte Carlo-based simulation in which 90 Y quantitation is compared to that of 18 F [ 99 ]. It was found that, relative to 18 F, the image quality was only slightly poorer in 90 Y for a similar positron emission rate.…”
Section: Reviewmentioning
confidence: 75%
“…They are summarised in Table 5. Some studies focused on qualitative and detection performances through image quality reports [34,52,54,55,57,[59][60][61], such as the CRC and the background variation (BV) following the NEMA NU-2 standards and guidelines [33]. Some other studies focused on a more quantitative evaluation on activity concentrations trough RC AC [22, 34, 36, 44, 48-51, 53, 56, 58, 59, 61].…”
Section: Discussionmentioning
confidence: 99%
“…Elschot et al [52] in 2013 showed through DVH that 90 Y dosimetry is more precise for PET than SPECT imaging. Strydhorst et al [55] in 2016 showed in their study that the bremsstrahlung radiation had negligible effects on PET-image image quality using Monte Carlo simulations. D'Arienzo et al [56] in 2017 concluded that the post-SIRT dosimetry is possible even in conditions of low statistics and high random fraction, granted that accurate PET calibration is performed and acquisition durations are sufficiently long.…”
Section: Discussionmentioning
confidence: 99%